POLA ASUH ORANG TUA DEMOKRATIS, INTERAKSI EDUKATIF, DAN MOTIVASI BELAJAR SISWA - Dalas, Muka; -, Emosda; -, Ekawarna (Program Magister Teknologi Pendidikan Universitas Jambi, 2012)
This article is aimed to study the relationship between democratic parenting pattern, educative interaction, learning motivation of primary school students. Two independent variables in this experimental research are democratic parenting pattern and educational interactions, and the dependent variable is students' motivation. From the correlation analysis it can be stated that (1) there is a positive and significant relationship between parenting pattern and student motivation (r=0,559). Democratic parenting pattern and related closely to student’s learning motivation; (2) there is a positive and significant relationship between students interaction and student motivation (r=0,720). Students interaction gives a strong impact on improving student’s motivation; and (3) there is a positive and significant relationship between parenting pattern, student’s interaction and motivation (0,2109). The democratic parenting pattern and educational interaction give a strong impact on improving student’s motivation. Kata kunci: democratic parenting, educational interaction, learning motivation